Formation of Polyatomic Cations of Tellurium, Sulfur and Antimony in Flourosulfuric Acid - Vaidya, Om C. (My University, 1971)
Polyatomic cations of tellurium, sulfur and antimony have been studied in HS03F. Tellurium metal can be oxidised with S206F2 in HS03F to the (+1) oxidation state. The cryoscopic measurements in HS03F suggest that the cation is not Te2^2+ but a higher polymer. Sulfur can be oxidised to the (+1/8), (+1/4) and (+1/2) oxidation states in acidic solvents. The cations S16^2+ and S8^2+ have been identified in the solutions from cryoscopic conductivity measurements and UV-visible absorption spectroscopy.
UV-visible absorption spectra, cryoscopy and conductivity measurements show that antimony metal is oxidised by HS03F to the (+1) and (+3) oxidation states. The compounds of antimony in the (+1) oxidation states have been prepared. Sb(I) reduces HS03F to sulfur cations and elemental sulfur. No evidence has been obtained for an oxidation state of antimony lower than (+1).
Title: Formation of Polyatomic Cations of Tellurium, Sulfur and Antimony in Flourosulfuric Acid, Author: Om C. Vaidya, Location: Thode